Atomic-size effect and solid solubility of multicomponent alloys. (1st January 2015) - Wang, Zhijun; Huang, Yunhao; Yang, Yong; Wang, Jincheng; Liu, C.T.
Abstract : In physical metallurgy, solid solubility of alloys is known to play a vital role in determining their physical/mechanical properties. Hume–Rothery rules show the great effect of size difference between solvent and solute atoms on the solid solubility of binary alloys. However, modern multicomponent systems, such as high-entropy alloys, defy the classic atomic size effect due to the absence of solvent and/or solute atoms. Here, we propose an effective atomic size parameter by considering atomic packing misfitting in multicomponent systems.